2016
DOI: 10.1177/2211068215601637
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Genotyping Using Acoustic Droplet Ejection for Enhanced Data Reproducibility, Superior Throughput, and Minimized Cross-Contamination

Abstract: Genetically engineered animal models are major tools of a drug discovery pipeline because they facilitate understanding of the molecular and biochemical basis of disease. These highly complex models of human disease often require increasingly convoluted genetic analysis. With growing needs for throughput and consistency, we find that traditional aspiration-anddispense liquid-handling robots no longer have the required speed, quality, or reproducibility.We present an adaptation and installation of an acoustic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Other experimental approaches to reduce the impacts of well-to-well contamination bear further investigation. These might include use of higher-fidelity liquid handling approaches [33], or broader adoption of unique-per-sample positive control spike-ins to allow the direct observation and statistical disambiguation of cross-contamination [34]. Methods which rely on identifying and subtracting putative contaminants from datasets need to be used with extreme caution, particularly if the identified sequence variants are present in primary samples.…”
Section: Discussionmentioning
confidence: 99%
“…Other experimental approaches to reduce the impacts of well-to-well contamination bear further investigation. These might include use of higher-fidelity liquid handling approaches [33], or broader adoption of unique-per-sample positive control spike-ins to allow the direct observation and statistical disambiguation of cross-contamination [34]. Methods which rely on identifying and subtracting putative contaminants from datasets need to be used with extreme caution, particularly if the identified sequence variants are present in primary samples.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha- and beta-diversity measures were highly correlated across methods. While we did not explicitly test well-to-well contamination, other studies have demonstrated that contamination may be lower when using acoustic liquid handlers over traditional pipette-based liquid handlers for molecular assays while also having higher dispensing accuracy ( 9 ). Finally, while we demonstrate the utility of this method for the 16S rRNA gene, this method could easily be applied to any amplicon based library preparation method.…”
Section: Discussionmentioning
confidence: 99%
“…These types of tipless transfers possess the major benefit of eliminating cross-contamination issues. Compared to tip-based dispending, acoustic liquid handling has also been shown to lead to more accurate biological activity in pharmacological assays [33]. This might be due to possible interactions between additives in the plastic tips and reagents, which have been observed to possibly leach from laboratory plasticware [33].…”
Section: Overview Of Technologiesmentioning
confidence: 99%